(untitled) (Research, Society and Development, 2022)
Spodoptera frugiperda worm represents a major problem in maize crop and the use of insecticide is the most used control measure. The main problems related to this practice are related to the development of resistant worm lineages. Studies of plants with insecticidal properties to control this pest have grown due to the lower impacts of their use. The objective of this study was to evaluate the insecticidal potential of the plants Chrysanthemum morifolium (Asterales: Asteraceae), Dieffenbachia picta (Alismatales: Araceae), Sansevieira trifasciata (Asparagales: Asparagaceae) and Tagetes erecta (Asterales: Asteraceae) on Spodoptera frugiperda worm mortality. The worms were raised in the laboratory, and kept under artificial diet. For the plant bioassays third instar larvae were used in two methods, control contat and ingestion. The evaluation period was five days. Individuals who when touched with the tip of a brush in the last abdominal segments did not respond with coordinated movements were considered dead. All four evaluated plants C. morifolium, D. picta, S. trifasciata and T. erecta caused the death of a low number of S. frugiperda worms. The C. morifolium and S. trifasciata plants, despite the low mortality rate, were those that stood out with 13.19% and 12.49% dead worms at the 70% concentration at the end of the evaluations. The method of action varied between the two plants and for C. morifolium the method of contact and ingestion were statistically the same from day three while for S. trifasciata the method of contact was better and resulted in the death of more caterpillars. It is concluded that in spite of the low mortality with the extracts, the plants C. morifolium and S. trifasciata presented higher mortality than the others. Note that the extract is obtained in a crude way, having its minimum efficiency evaluated.